2006
DOI: 10.1111/j.1600-051x.2006.01002.x
|View full text |Cite
|
Sign up to set email alerts
|

Does periodontal care improve glycemic control? The Department of Veterans Affairs Dental Diabetes Study

Abstract: No significant benefit was found for periodontal therapy after 4 months in this study; trends in some results were in favour of periodontal treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
149
2
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(166 citation statements)
references
References 28 publications
11
149
2
4
Order By: Relevance
“…Our previous study also showed the beneficial effect of periodontal therapy on diabetes with acceptable glycemic control (HbA1c between 6.5% and 7.5%) (13), in contrast to the studies of Jones et al (14) and Lalla et al (15).…”
Section: Introductioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Our previous study also showed the beneficial effect of periodontal therapy on diabetes with acceptable glycemic control (HbA1c between 6.5% and 7.5%) (13), in contrast to the studies of Jones et al (14) and Lalla et al (15).…”
Section: Introductioncontrasting
confidence: 53%
“…These findings indicate that inflammation is involved in the pathogenesis of IR and T2DM, which is regarded as key processes in the mechanism of T2DM (8). However, Jones et al indicated that periodontal therapy has no statistically significant effect on glycemic control (14). This could be attributed to considerable differences in methodology, sample sizes and composition of the groups included in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Intervention studies of the effect of nonsurgical periodontal treatment in diabetic patients generally show improved periodontal status, while results concerning changes in glycemic status are rather contradictory. Some found significant improvements in glycemic control (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19); others did not (20)(21)(22)(23)(24)(25)(26). Meta-analyses of intervention studies indicate a need for additional trials to clarify this relationship (27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that periodontal treatment significantly improved glycemic conditions (22)(23)(24)(25). A recent meta-analysis of the efficacy of periodontal treatment on glycemic control in diabetic patients suggested that such treatment could lead to significant reductions in HbA1c (26).…”
Section: Effects Of Periodontal Treatment On Diabetesmentioning
confidence: 99%